Comparative immunogenicity and efficacy of thermostable (lyophilized) and liquid formulation of anthrax vaccine candidate AV7909. Issue 43 (8th October 2019) - Autumn Smiley, M.; Sanford, Daniel C.; Triplett, Cheryl A.; Callahan, Daniel; Frolov, Vladimir; Look, Jee; Ruiz, Christian; Reece, Joshua J.; Miles, Aaron; Ruiz, Ericka; Ionin, Boris; Shearer, Jeffry D.; et al.
Abstract: The anthrax vaccine candidate AV7909 is being developed as a next-generation vaccine for a post-exposure prophylaxis (PEP) indication against anthrax. AV7909 consists of the anthrax vaccine adsorbed (AVA) (Emergent BioSolutions Inc., Lansing, MI) bulk drug substance adjuvanted with the immunostimulatory oligodeoxynucleotide (ODN) compound, CPG 7909. The addition of CPG 7909 to AVA enhances both the magnitude and the kinetics of antibody responses in animals and human subjects, making AV7909 a suitable next-generation vaccine for use in a PEP setting. Emergent has produced a thermostable (lyophilized) formulation of AV7909 vaccine utilizing drying technology. The purpose of the study described here was to assess the immunogenicity and efficacy of the lyophilized formulation of the AV7909 vaccine candidate as compared with the liquid formulation in the guinea pig general-use prophylaxis (GUP) model. The study also provides initial information on the relationship between the immune response induced by the thermostable formulation of the vaccine, as measured by the toxin neutralization assay (TNA), and animal survival following lethal anthrax aerosol challenge. Results demonstrated that there were no significant differences in the immunogenicity or efficacy of lyophilized AV7909 against lethal anthrax spore aerosol challenge in the guinea pig model as compared to liquid AV7909. For both vaccine formulations, logistic regression modeling showed that the probability of survival increased as the pre-challenge antibody levels increased.